Pengaruh religiusitas dan dukungan sosial terhadap psychological well-being pada mahasiswa santri - Khoerani, Jani; Lestari, Endang Suci; Azizah, Nur; Wulandari, Triana (Fakultas Psikologi Universitas Hang Tuah, 2024)
This study seeks to explore the impact of religiosity and social support on the psychological well-being of students in Islamic boarding schools. This study involved 96 high school students in Indonesia. The method was quantitative. Multiple linear regression analysis and hierarchical regression were used to test the hypotheses. The results of multiple linear regression analysis show that religiosity and social support affect psychological well-being. Partial analysis results show a very large positive relationship between social support religiosity and psychological well-being. Hierarchical regression results showed that, when tested together with religiosity and social support, gender had a significant effect on psychological well-being. Gender also influences the strengths and weaknesses of the influence of religiosity and social support on psychological well-being.